Characterization and expression of a cloned tetracycline resistance determinant from the chromosome of Streptococcus mutans. - Tobian, J A (1984)
A chromosomal tetracycline resistance (Tcr) determinant previously cloned from Streptococcus mutans into Streptococcus sanguis (Tobian and Macrina, J. Bacteriol. 152:215-222, 1982) was characterized by using restriction endonuclease mapping, deletion analysis, and Southern blot hybridization. Deletion analysis allowed localization of the Tcr determinant to a 2.8-kilobase region of the originally cloned 10.4-kilobase sequence. This cloned determinant hybridized to a representative of the tetM class of streptococcal Tcr determinants but not to representatives of the tetL and tetN classes and, like other tetM determinants, mediated high-level resistance to tetracycline and low-level resistance to minocycline. A portion (approximately 3 kilobases) of the isolated streptococcal fragment was subcloned into Escherichia coli, where it conferred resistance to tetracycline and minocycline. Two proteins with apparent molecular weights of 33,000 and 35,000, encoded by the S. mutans DNA, were synthesized in E. coli minicells. Insertion of DNA into a unique SstI site of the cloned S. mutans fragment resulted in inactivation of Tcr expression in E. coli and S. sanguis, as well as loss of production of both the 33,000- and 35,000-dalton proteins in E. coli minicells. Incubation of minicells in subinhibitory concentrations of tetracycline did not result in changes in the levels of synthesis of either protein. Our data suggest that at least one of these proteins is involved in the expression of Tcr.